Structural Basis for the Interaction of a Hexameric Replicative Helicase with the Regulatory Subunit of Human DNA Polymerase α-Primase - Zhou, Bo (American Society for Biochemistry and Molecular Biology, 2012)
DNA polymerase α-primase (Pol-prim) plays an essential role in eukaryotic DNA replication, initiating synthesis of the leading strand and of each Okazaki fragment on the lagging strand. Pol-prim is composed of a primase heterodimer that synthesizes an RNA primer, a DNA polymerase subunit that extends the primer, and a regulatory B-subunit (p68) without apparent enzymatic activity. Pol-prim is thought to interact with eukaryotic replicative helicases, forming a dynamic multiprotein assembly that displays primosome activity. At least three subunits of Pol-prim interact physically with the hexameric replicative helicase SV40 large T antigen, constituting a simple primosome that is active in vitro. However, structural understanding of these interactions and their role in viral chromatin replication in vivo remains incomplete. Here, we report the detailed large T antigen-p68 interface, as revealed in a co-crystal structure and validated by site-directed mutagenesis, and we demonstrate its functional importance in activating the SV40 primosome in cell-free reactions with purified Pol-prim, as well as in monkey cells in vivo.